Sustained polymorphic ventricular tachycardia in a calf - Amir Naseri; Merve Ider; Mahmut Ok (Eurasian Journal of Veterinary Sciences)
Sustained polymorphic ventricular tachycardia is a type of ventricular dysrhythmias which originated from more than one focus in ventricle and may lead to fatal arrhythmias like as ventricular fibrillation and sudden death. A seven days old female Holstein calve was referred to the Large Animals Hospital of the Faculty of Veterinary Medicine of Selcuk University with a history of sudden collapse. Electrocardiography examination showed sustained polymorphic ventricular tachycardia. Cardiac damage suspicion confirmed by elevation in serum cardiac troponin I (cTnI), creatine kinase-MB (CK-MB) and creatine phosphokinase (CPK) concentrations as cardiac damage enzymes.